2004
DOI: 10.1007/s00595-004-2845-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Hyaluronic Acid Level as a Good Predictor of Posthepatectomy Complications

Abstract: Our findings indicate that the preoperative serum HA level is a good predictor of postoperative complications in patients who undergo hepatectomy for injured liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…The findings of our study and those of others showed that serum HA concentrations correlated inversely with measurements of functional liver reserve and the degree of hepatic fibrosis, suggesting that measuring the HA level might be useful for monitoring liver damage or predicting postoperative complications after hepatic resection [18,23].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The findings of our study and those of others showed that serum HA concentrations correlated inversely with measurements of functional liver reserve and the degree of hepatic fibrosis, suggesting that measuring the HA level might be useful for monitoring liver damage or predicting postoperative complications after hepatic resection [18,23].…”
Section: Discussionsupporting
confidence: 77%
“…Damage to the hepatic endothelial cells results in a high serum HA level [18,23], which is thought to be a marker of hepatic fibrosis. If endothelial cell function in the injured liver deteriorates [23], the serum HA level could be a useful marker of nonparenchymal liver cell function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary end point was the development of postoperative hepatic insufficiency. Postoperative hepatic insufficiency was defined as persistent hyperbilirubinemia (total bilirubin level N5 mg/dl for more than 5 days after surgery) or postoperative death without other causes [19,20]. The secondary end points were the performance of ADC values in the assessment of liver fibrosis, the reliability of ADC values between the two hepatic lobes, and the intra-and interobserver reliability of ADC values.…”
Section: Patientsmentioning
confidence: 99%